Pengaruh Pengetahuan, Penerapan Safety Talk dan Masa Kerja terhadap Kepatuhan Penggunaan Alat Pelindung Diri (APD) pada Pekerja Bagian Piping di PT Berkat Karunia Phala Duri Riau Tahun 2024: Penelitian - Rupina Kanasia Situmorang; Neni Ekowati Januariana; Santa Tioria Sinaga (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Compliance with Personal Protective Equipment (PPE) regulations denotes the extent to which workers adhere to the utilisation of PPE that aligns with the prescribed standards and the potential hazards present in the work environment. The compliance with the use of PPE is influenced by the individual worker, taking into account their knowledge, participation in safety talks, tenure, length of service and attitude. Based on preliminary assessment of ten workers found that four of them did not comply with the usage of PPE owing to pain, heat, inconvenience, and delays in job performance when wearing full PPE. The objective of study was to determine the factors that influence compliance with the use of PPE at PT. Berkat Karunia Phala Duri Riau. This research design employed a cross-sectional analytical survey. The entire workforce comprising 36 individuals, was selected as the research sample. The data were analysed using univariate, bivariate and multivariate techniques. The results of the multivariate analysis with the Logistic Regression test showed that there was an influence between knowledge (p = 0.017) and length of service (p = 0.040) on compliance with the use of PPE. There was no influence between the implementation of safety talk (p = 1.000) on compliance with the use of PPE. The most influential factor was knowledge with Exp (B) 22.884.